Producing alcohol and other drugs as a policy 'problem': A critical analysis of South Africa's 'National Drug Master Plan' (2013-2017) - Pienaar, Kiran; Savic, M. (2015)
© 2015 Elsevier B.V. Background: The strong symbolic value of illicit drug use makes it a contested issue, which attracts mixed public opinion, intense media attention and close political scrutiny. This means that the formulation of plausible, authoritative policies governing illicit drugs must navigate fraught political terrain. In a country like South Africa with its long unique history of institutionalised oppression of the black majority, the issues confronting drug policy are particularly complex and the need for carefully formulated policy responses especially urgent. Yet despite this, the area of drug policy development in South Africa has received little scholarly attention to date. Methods: This paper explores the complexities of policymaking in the South African context by drawing on feminist scholar Carol Bacchi's poststructuralist approach to policy analysis, which focuses on how policy helps to produce the problems it purports to solve. Taking as its empirical focus, South Africa's current drug policy, the third National Drug Master Plan (NDMP), 2013-2017, the paper analyses how the policy constitutes the 'problem of alcohol and other drugs' (AODs). Results: We identify three central policy proposals through which specific problematisations emerge: (1) the proposal that drug use is a global issue requiring a coordinated policy response, (2) appeals to evidence-based policy proposals and (3) the proposal that AOD 'use' and 'abuse' be treated interchangeably. We suggest that these proposals reveal a tendency towards inflating the 'problem of AODs' and thus work to justify punitive policy measures. Conclusions: In an effort to explore the implications of particular problematisations for effecting social change, we clarify the ways in which the policy may work to undermine the interests of those it seeks to aid by reinforcing stigma and marginalisation.